BCL2l10 is overexpressed in melanoma downstream of STAT3 and promotes cisplatin and ABT-737 resistance - Quezada, Maria Josefina (2020)
The anti-apoptotic proteins from the Bcl-2 family are important therapeutic targets since they convey resistance to anticancer regimens. Despite the suspected functional redundancy among the six proteins of this subfamily, both basic studies and therapeutic approaches have focused mainly on BCL2, Bcl-xL, and MCL1. The role of BCL2L10, another member of this group, has been poorly studied in cancer and never has been in melanoma. We describe here that BCL2L10 is abundantly and frequently expressed both in melanoma cell lines and tumor samples. We established that BCL2L10 expression is driven by STAT3-mediated transcription, and by using reporter assays, site-directed mutagenesis, and ChIP analysis, we identified the functional STAT3 responsive elements in the BCL2L10 promoter. BCL2L10 is a pro-survival factor in melanoma since its expression reduced the cytotoxic effects of cisplatin, dacarbazine, and ABT-737 (a BCL2, Bcl-xL, and Bcl-w inhibitor). Meanwhile, both genetic and pharmacological inhibition of BCL2L10 sensitized melanoma cells to cisplatin and ABT-737. Finally, BCL2L10 inhibited the cell death upon combination treatments of PLX-4032, a BRAF inhibitor, with ABT-737 or cisplatin. In summary, we determined that BCL2L10 is expressed in melanoma and contributes to cell survival. Hence, targeting BCL2L10 may enhance the clinical efficacy of other therapies for malignant melanoma.